2021
DOI: 10.1016/j.apr.2020.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and critical air pollutant assessment during and after COVID-19 lockdowns: Evidence from pandemic hotspots in China, the Republic of Korea, Japan, and India

Abstract: The COVID-19 virus outbreak has been declared a “global pandemic”. Therefore, “lockdown” was issued in affected countries to control the spread of the virus. To assess air pollution during and after lockdowns, this study selected pandemic hotspots in China (Wuhan), Japan (Tokyo), Korea (Daegu), and India (Mumbai) and compared the Air Quality Index (AQI) in these areas for the past three years. The results indicated that air pollution levels were positively correlated with a reduction in pollutant levels during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 24 publications
2
29
0
1
Order By: Relevance
“…A decline of pollutants NO 2 , PM 2.5 , and PM 10 in many cases illustrate the clear benefit of forced lockdowns allowing the evaluation of the impact of pollutant concentration, and providing a better understanding of the impact industrial site activities have on air quality changes. All the study results shown above suggest that a direct improvement of air quality during the lockdown periods was visible in all countries [20,29,72]. A significant impact of COVID-19 lockdown on air quality improvement was found in all 4 countries and the Northern region of Italy, including a significant decrease in NO 2 concentration (see Figures 4-8).…”
Section: Discussionmentioning
confidence: 68%
“…A decline of pollutants NO 2 , PM 2.5 , and PM 10 in many cases illustrate the clear benefit of forced lockdowns allowing the evaluation of the impact of pollutant concentration, and providing a better understanding of the impact industrial site activities have on air quality changes. All the study results shown above suggest that a direct improvement of air quality during the lockdown periods was visible in all countries [20,29,72]. A significant impact of COVID-19 lockdown on air quality improvement was found in all 4 countries and the Northern region of Italy, including a significant decrease in NO 2 concentration (see Figures 4-8).…”
Section: Discussionmentioning
confidence: 68%
“…We calculated the air quality index (AQI) ( Ministry of Environmental Protection of China, 2012 ) to evaluate the air quality characteristics in Wuhan from January to April/May during 2017–2020. AQI is an effective method for describing urban air quality and is widely used in many countries ( Tan et al, 2021 ; Heidarinejad et al, 2018 ; Hu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…This allowed further studies to evaluate air quality later on in the pandemic as restrictions were eased, and compare these results to the air quality during the lockdown phase. These analyses agreed that the air quality improvements achieved during the lockdown period were only temporary as pollutant levels slowly increased again as lockdowns were lifted (Kumari et al, 2020; Liu et al, 2020a , Sulaymon et al, 2021 , Hu et al, 2021 ). Most previous studies compared trends before, during, and after policy implementation to investigate possible changes associated with mitigation measures, and focused on the short-term impacts of these policies.…”
Section: Introductionmentioning
confidence: 66%